Analysis of Sediment Transport Patterns in Rivers Using Hydrological and Geomorphological Approaches - Nenny (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Rivers as a crucial element in the hydrological system provide water for various human, agricultural, industrial and ecosystem needs. However, natural phenomena such as erosion and sedimentation can threaten the stability of rivers and the surrounding environment. This study outlines the impacts of sedimentation on the Bailang River and Sario River, highlighting the importance of hydrological and geomorphological approaches in understanding sediment transport patterns. Land conversion along the Bailang River has caused narrowing of the river channel and sedimentation, increasing the risk of flooding. Hydrological analysis shows that changes in water discharge and rainfall influence sediment transport in the Bailang River. In the Sario River, flooding and erosion affect river morphology, with large water discharges being the main cause of flooding. The hydrological approach considers factors such as water discharge and rainfall, while the geomorphological approach considers landforms, topography and river flow patterns. The analysis shows that interactions between hydrological and geomorphological factors influence sediment transport patterns in both rivers. The results of this research provide an in-depth understanding of sediment transport patterns in the Bailang River and Sario River. The implications include planning effective river management strategies, mitigating erosion, sedimentation and flood risk, as well as better spatial planning in riverbank areas. The contribution of this research is important for sustainable river management and environmental protection. Understanding sediment transport patterns provides the basis for developing more effective erosion and sedimentation mitigation strategies, with the aim of minimizing their negative impacts on rivers and their environment.